Diversity of non‐structural carbohydrates in grasses (Poaceae) from Brazil. (29th June 2012) - Moraes, M. G.; Chatterton, N. J.; Harrison, P. A.; Filgueiras, T. S.; Figueiredo‐Ribeiro, R. C. L.
Abstract Non‐structural carbohydrates (NSC) are the primary energy available for growth and dry‐mass production in forage grasses. They are also associated with tolerance to environmental stresses, including drought. Soluble carbohydrates, especially fructans of temperate forage grasses, have been extensively studied; however, little is known about NSC of tropical grasses. These plants are abundant in the Cerrado, a savanna‐like vegetation with a definite seasonality in rainfall distribution. Such an environment presents an ideal condition for the occurrence of fructans. However, the present analysis of carbohydrates in aerial parts of twenty‐four tropical grass species, mainly from the Panicoideae subfamily in the Cerrado, shows a distinctively different NSC profile when compared with temperate grasses. Free glucose and starch are common NSC found in most plant organs. However, free fructose and sucrose‐based oligosaccharides were only found in very low amounts. Sucrose was detected in higher amounts only in stems. A linear series of malto‐oligosaccharides was found in leaf blades, sheaths and stems of most of the Cerrado grasses, except for those from the Andropogoneae tribe. These results indicate a diversity of regulatory pathways of NSC metabolism in tropical forage grasses from the Cerrado.